Impact of GMO’S on environment and human health - Godheja, Jai (Recent Research in Science and Technology, 2013)
<span style="font-size: 10.0pt; line-height: 115%; font-family: "Arial Narrow","sans-serif"; mso-fareast-font-family: BatangChe; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 1.0pt; mso-fareast-language: KO; mso-bidi-font-weight: bold;">Genetic pollution is the term of genetics in which the genetic information is transferred in to the organisms where it is not needed or where this information never existed before. Genetic pollution is a controversial[1][2] term for uncontrolled [3][4] gene flow into wild populations.This flow of genetic information is usually undesired and cannot be controlled. The flow of genetic information usually takes place between the genetically modified organisms into the organisms which are not genetically modified. Genetic modification of genome uses techniques like site directed mutagenesis, selective breeding, somaclonal variations, horizontal gene transfer (transgenesis), cisgenesis and their modifications. The causes of gene pollution may be Cross-breeding of GM crops with the wild varieties by cross pollination, consumption of GM foods and improper disposal of unsuccessful GM crops. The transfer of modified genes by wind-borne pollen might wipe out countless species of organisms. Microbiologists have come up with an important point that if genetic modification is carried out extensively, new viruses with greater potential to harm mankind may evolve anytime, and the probability of this occurring can be quite high. This form of dangerous biotechnology will only benefit largely towards the GM crop farmers in form of monetary gain. According to relevant statistics, farmers would save more than US$3.3 billion annually on herbicides, insecticides, and fungicides. So come to think of it. Is it worthwhile to become the guinea pigs just to save a few bucks, while those farmers are sitting down there counting their huge earnings without inflicting any risks on themselves? While some countries have banned GMOs or placed a moratorium on their release, others are increasing both investment levels and land area devoted to cultivating genetically modified (GM) crops. In 2006, GM crops were grown commercially by 10.3 million farmers (9.3 million resource-poor small farmers in developing countries) in 22 countries, on 102 million hectares - about 4 per cent of total arable land worldwide [5]